Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1585/pfr.6.2401058
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Quantum Mechanical ∇B Drift

Abstract: We have solved the two-dimensional time-dependent Schrödinger equation for a single particle in the presence of a nonuniform magnetic field for initial speeds of 10-100 m/s. By linear extrapolation, it is shown that the variance, or the uncertainty, in position would reach the square of the interparticle separation n −2/3 with a number density of n = 10 20 m −3 in a time interval of the order of 10 −4 sec. After this time the wavefunctions of neighboring particles would overlap, as a result the conventional cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…This normalized grid size is sufficiently small to use as noted in Ref. [1]. Table 1 Normalized parameter for mass of the particle, charge, magnetic flux density, velocity, length and time.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This normalized grid size is sufficiently small to use as noted in Ref. [1]. Table 1 Normalized parameter for mass of the particle, charge, magnetic flux density, velocity, length and time.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In the previous paper [1], we have shown that the quantum mechanical variance in position may reach the square of the interparticle separation in a time interval of the order of 10 −4 sec for typical magnetically confined fusion plasmas with a number density of n ∼ 10 20 m −3 and a temperature of T ∼ 10 keV.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…(1) with an appropriate initial condition in x-y plane, using the finite difference method (FDM) in space with the Crank-Nicolson scheme [1][2][3][4][5].…”
Section: Numerical Analysismentioning
confidence: 99%
“…The charged particles drift in the presence of a magnetic field B, the drifts include ∇B drift, curvature drift and E × B drift if there exist an electric field E. The two-dimensional time-dependent Schrödinger equation have been already solved for a charged particle in the presence of a non-uniform magnetic field and a uniform electric field, in which it was shown that the variance, or the uncertainty, in position σ 2 r (t) grows with time [1][2][3][4][5]. For the typical fusion plasma with a temperature T ∼ 10 keV and a number density of n ∼ 10 20 m −3 , the standard deviation σ r (t) would reach the interparticle separation n −1/3 in a time interval of the order of 10 −4 sec.…”
Section: Introductionmentioning
confidence: 99%